Unextendible Entangled Bases With a Fixed Schmidt Number Based on Generalized Weighing Matrices - Tao, Yuan-Hong; Yong, Xin-Lei; Bai, Ya-Ru; Xu, Dan-Ni; Wu, Shu-Hui (Frontiers in Physics, 2022)
We systematically study the constructions of unextendible entangled bases with fixed Schmidt number k (UEBk) in bipartite system C^dC^d'. Motivated by the methods of [J. Phys. A 52: 375303, 2019], we construct (dd'-v)-member UEBks in C^dC^d' by using generalized weighing matrices, thus generalize the results of [arXiv: 1909.10043, 2020]. We also present the corresponding expressions of our constructions and graphically illustrate UEB3s in C^5C^6 and C^6C^6.